Določitev imenske moči motorja s poskusom pospeševanja vozila - Medica, Vladimir (Strojniški vestnik, 2001)
We present a newly developed method, devices and a procedure for determining an engine's wide open throttle(WOT) performance from a vehicle speed-up test. The control of an engine's performance often requires that the engine is dismantled from the vehicle in order to be able to conduct engine braking test on a bench or it is necessary to built a torque meter into the drive train of the vehicle. The presented method is very simple and reliable. The method enables us to derive the WOT performance from three probes, one vehicle deceleration test and two vehicle acceleration tests. The collected test data are processed together with only limited vehicle input data to derive accurate engine-performance figures.
Keywords: motorji avtomobilski; karakteristike motorjev; modeli matematični; meritve; avtomobilski motorji; moč motorja; matematični modeli